So little time. Too good to be true - Butcher, Nancy; Olsen, Mary-Kate, 1986-; Olsen, Ashley, 1986- (New York : HarperEntertainment, 2002)
Chloe and Riley Carlson struggle with sewing and cooking while juggling boyfriends and boyfriends' ex-girlfriends.
"A Parachute Press book.".
"Based on the hit TV series"--Cover.
All Ages.
Keywords: Dating (Social customs) -- Juvenile fiction; Twins -- Juvenile fiction; Teenagers -- Juvenile fiction; Twins -- Fiction; Sisters -- Fiction; Dating (Social customs) -- Fiction; Cookery -- Fiction; Sewing -- Fiction